Price Regulation of the Residential (Retail) Energy Market: Comparing the practices of the United States of America with the European Commission’s “Clean Energy Package” - Nyikos, Attila (Közigazgatási és Infokommunikációs Jogi PhD Tanulmányok, 2025)
Directive (EU) 2019/944 of the European Parliament and of the Council of 5 June 2019 on common rules for the internal market in electricity, which amends Directive 2012/27/EU, advocates for the phasing out of regulated household electricity prices in favour of a fully liberalised retail electricity market. According to the author’s position, the removal of regulated end-user prices adversely affects Hungarian household consumers. This stance is supported by the economic argument that genuine competition in the household electricity market can only function effectively—thus should only be permitted by law—under specific conditions: the presence of a developed economy with abundant domestically sourced energy resources; high individual income levels, which enhance consumer engagement; widespread adoption of energy-efficient, cost-effective technologies and innovations at the household level. Only where these criteria are met can liberalisation result in reduced household energy costs and increased energy savings over the long term. In all other contexts, even partial liberalisation of the retail market tends to trigger a spiralling increase in household energy prices.